Pachymic acid protects hepatic cells against oxygen-glucose deprivation/reperfusion injury by activating sirtuin 1 to inhibit HMGB1 acetylation and inflammatory signaling - Chengbiao Xue; Zhigao Xu; Zhongzhong Liu; Cheng Zeng; Qifa Ye (Chinese Journal of Physiology, 2023)
Ischemia-reperfusion injury is an important cause of liver injury occurring during liver transplantation. It is usually caused by inflammatory response and oxidative stress-induced oxidative damage. Pachymic acid (PA) has various biological activities such as anti-inflammatory, antioxidant and anti-cancer. However, the action mechanism of PA in hepatic ischemia-reperfusion injury is currently unknown. In this study, liver cells were subjected to oxygen-glucose deprivation/reperfusion (OGD/R) to simulate a hepatic ischemia-reperfusion injury model. The binding relationship between PA and sirtuin 1 (SIRT1) was analyzed by molecular docking. Cell viability was detected by Cell Counting Kit-8. Expression levels of SIRT1 and high mobility group box 1 (HMGB1) were detected by western blot. Subsequent levels of inflammatory factors were detected by related kits and western blot. Meanwhile, related kits were used to examine levels of oxidative stress markers including reactive oxygen species, malondialdehyde, superoxide dismutase and cytotoxicity-associated lactate dehydrogenase. Finally, cell apoptosis was detected by flow cytometry and western blot. The results showed that PA significantly ameliorated OGD/R-induced decrease in SIRT1 expression, increase in HMGB1 acetylation and HMGB1 translocation. Moreover, the elevated levels of inflammatory factors, oxidative stress indexes and cell apoptosis upon exposure to OGD/R were reversed by PA treatment. Moreover, the addition of SIRT1 agonist and inhibitor further demonstrated that PA exerted the aforementioned effects in OGD/R-exposed cells by targeting SIRT1. Thus, the present study revealed the mechanism by which PA ameliorated OGD/R-induced hepatic injury via SIRT1. These results might provide a clearer theoretical basis for the targeted treatment of OGD/R-induced hepatic injury with PA.